2020
DOI: 10.31110/2413-1571-2020-023-1-020
|View full text |Cite
|
Sign up to set email alerts
|

Formation of skills to visualize of future physics teacher: results of the pedagogical experiment

Abstract: Формулювання проблеми. Проблема формування умінь візуалізувати навчальний матеріал є актуальними для вчителів природничо-математичних спеціальностей, оскільки їхня професійна діяльність пов'язана з поясненням абстрактних понять, логіки міркувань або процесів, пояснення природних явищ на мікро-і макро-рівнях. Мета: описати результати педагогічного експерименту з формування у майбутніх учителів фізики умінь візуалізувати начальний матеріал. Матеріали і методи: Для виконання завдань дослідження використано теорет… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These results are from previous research they are ducted by (Semenikhina et al, 2020). The five assessment points found that they could produce prediction models with up to 80% accuracy with just three formative assessment data.…”
Section: Resultssupporting
confidence: 79%
“…These results are from previous research they are ducted by (Semenikhina et al, 2020). The five assessment points found that they could produce prediction models with up to 80% accuracy with just three formative assessment data.…”
Section: Resultssupporting
confidence: 79%